1992
DOI: 10.1002/ijc.2910500103
|View full text |Cite
|
Sign up to set email alerts
|

Association between restriction fragment length polymorphism of the L‐myc gene and lung metastasis in human breast cancer

Abstract: EcoRI restriction fragment length polymorphism (RFLP) of the L-myc gene was examined in leukocyte DNAs isolated from 381 breast cancer patients. No differences in the patterns of L-myc RFLP were found between breast cancer patients and healthy individuals. However, among 97 patients who relapsed, a statistical correlation was found between L-myc RFLP and lung metastases (p less than 0.05). These results are in close agreement with previous findings in patients with cancer of the lung, bone or kidney, and sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…These results confirm those of Ikeda et al in colorectal cancer (1988), Tefre et al in lung cancer in Norway (1990), Ishizaki et al (1990) and Champeme et al (1992) in breast cancer, Saranath et al (1990) in oral cancer, Weston et al (1992) in lung cancer in the USA, Mironov et al (1994) in gastric cancer in Russia and Presti et al (1996) in renal cancer. On the other hand L-myc RFLP is correlated with the extent of metastasis of lung cancer in Japan (Kawashima et al, 1988(Kawashima et al, , 1992 and in renal cancer (Kakehi and Yoshida, 1989); Ishizaki et al (1990) also reported that the presence of the S-allele is associated with poor prognosis due to metastasic lesion in gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results confirm those of Ikeda et al in colorectal cancer (1988), Tefre et al in lung cancer in Norway (1990), Ishizaki et al (1990) and Champeme et al (1992) in breast cancer, Saranath et al (1990) in oral cancer, Weston et al (1992) in lung cancer in the USA, Mironov et al (1994) in gastric cancer in Russia and Presti et al (1996) in renal cancer. On the other hand L-myc RFLP is correlated with the extent of metastasis of lung cancer in Japan (Kawashima et al, 1988(Kawashima et al, , 1992 and in renal cancer (Kakehi and Yoshida, 1989); Ishizaki et al (1990) also reported that the presence of the S-allele is associated with poor prognosis due to metastasic lesion in gastric cancer.…”
Section: Discussionsupporting
confidence: 91%
“…The role of L-myc in cancer susceptibility has been implied by studies showing differences in genotype frequencies between cancer patients and controls Dolcetti et al, 1991;Crossen et al, 1994). The role of L-myc in prognosis has been suggested by studies showing that, among cancer patients, those that carry an Sallele (either LS or SS genotype) have earlier lymph node involvement or metastasis, or poorer survival than those who have genotype LL (Kakehi and Yoshida, 1989;Champeme et al, 1992;Kawashima et al, 1992). In contrast, Taylor et al (1993) reported a protective effect for the SS genotype in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…RR, relative risk; 95%CI, 95% confidence interval. myc in prognosis, studies on lung, 4) kidney, 2) stomach, 5) bone or soft tissue sarcomas, 8) and breast 9) showed that the presence of the S-allele (either LS or SS genotype) was associated with earlier lymph node involvement or metastasis, or a poorer prognosis than that of the LL genotype. However, a clear correlation between the L-myc RFLP and susceptibility to cancer or prognosis was found only in certain types of cancers or restricted populations.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered reports have suggested that individuals bearing the`short' (S) allele either have an increased incidence of certain tumors and/or that such tumors manifest a more aggressive behavior. The associated neoplasms include soft-tissue sarcomas (Kato et al, 1990), oral cancers (Saranath et al, 1990), colorectal cancers (Young et al, 1994), nonHodgkin's lymphoma (Crossen et al, 1994), breast cancer (Champeme et al, 1992), and non-SCLC lung cancer (Kawashima et al, 1988). In contrast, at least one report has suggested that the`SS' genotype protects against hepatocellular cancer (Taylor et al, 1993).…”
Section: Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%